UJI INDEPENDENSI KINERJA KEUANGAN TERHADAP KEBIJAKAN RIGHT ISSUE STUDI KASUS DI BURSA EFEK INDONESIA - Pujihastuti, Isti (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2015)
Investors are the investment partners. They should find supporting information for making investment desicions. This research will widen the academic knowledge and giving more information for the people, speciallyfor investor in the stock exchange. There are a lot of things that can be consoderation for investors, for instance,information of emiten corporation action. Right issue, not only to support investor, but also, teorritacally can giveinformastion that could cover both emiten and investor interest. Right issue is one of corporate policy or corporateaction in order to meet corporate goals, like bussiness expansion, increase liquidity, et cetera. Kuantitativeparadigm with descriptive method is used in this research. The research population are company that doing the rightissue in Indonesian Stock Exchange in the year 2012 ? 2014. With purposive sampling method, this research used 25companies as the sample research. Based on Kendal?s Tau Crosstab analysis, the result showed that DER, companysize and EAT significantly have the same direction with right issue policy, while company growth have differentdirection. Others variable, PBV and public minority, have no direction significantly to right issue. Since the data isnot normal and the result of significant test is not robust, so further, this research need others reference to supportthis research model